Análisis de las habilidades ortográficas en español del estudiantado universitario en Ecuador - Montesdeoca-Arteaga, Deborah Valerie; Palacios-Briones, Fátima Elizabeth; Gómez-Parra, María Elena; Espejo-Mohedano, Roberto (Universidad de Costa Rica, 2021)
Spelling is an essential skill for university students as it is part of the academic background acquired at both basic and intermediate levels. However, it is a challenge for teachers because students bring spelling deficiencies with them when they start their higher education stage. Thus, the objective of the study is to diagnose the spelling competence of first-year university students in specific courses at Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López (ESPAM MFL) in Ecuador. A diagnostic evaluation was applied to 438 students during the first two weeks of the academic period (October 2015 - March 2016). Descriptive theory and cross tables were used for data analysis, identifying spelling and vocabulary weaknesses. The demographic variables used during data analysis were sex, age and study origin. The results show that there is an alarming lack of application of spelling rules. The need to develop a program to improve the spelling of university students was identified. Therefore, strategies to solve this problem were designed, since good training in spelling is fundamental for the personal and professional development of university students.